2019
DOI: 10.1021/acs.analchem.9b00857
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Olfaction Ambient Mass Spectrometry

Abstract: Chemical ionization of organic compounds with negligible vapor pressures (VP) is achieved at atmospheric pressure when the proximal sample is exposed to corona discharge. The vapor-phase analyte is produced through a reactive olfaction process, which is determined to include electrostatic charge induction in the proximal condensed-phase sample, resulting in the liberation of free particles. With no requirement for physical contact, a new contained nano-atmospheric pressure chemical ionization (nAPCI) source wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…The lipids were prepared in chloroform, which was observed to favorably support ionization (see Figure S1). As part of our ongoing research in the development of contained ion sources, the current study represents that first time we have employed the coaxial spray mode where two spray capillaries deliver two liquid-phase reagents individually into the reaction cavity, the variable length of which allowed for customized mixing times between reagents (see the Supporting Information for details regarding the construction of the coaxial contained-electrospray (ES) platform). Recent experiments investigating the spray dynamics of the contained-ES source have shown that liquid reagents are first delivered into the reaction cavity as thin films, which are then dispersed into slow-moving (velocity of ∼10 mm/s) bulky droplets (average size 25 μm) upon nebulization with 100 psi N 2 gas.…”
Section: Resultsmentioning
confidence: 99%
“…The lipids were prepared in chloroform, which was observed to favorably support ionization (see Figure S1). As part of our ongoing research in the development of contained ion sources, the current study represents that first time we have employed the coaxial spray mode where two spray capillaries deliver two liquid-phase reagents individually into the reaction cavity, the variable length of which allowed for customized mixing times between reagents (see the Supporting Information for details regarding the construction of the coaxial contained-electrospray (ES) platform). Recent experiments investigating the spray dynamics of the contained-ES source have shown that liquid reagents are first delivered into the reaction cavity as thin films, which are then dispersed into slow-moving (velocity of ∼10 mm/s) bulky droplets (average size 25 μm) upon nebulization with 100 psi N 2 gas.…”
Section: Resultsmentioning
confidence: 99%
“…Aside from gas-phase chemical reactions, we believe the present configuration of the noncontact nESI/nPACI setup (coaxial) may allow surface-assisted ionization processes. This is exemplified by the detection of [M + H 2 + H] + species from methanol solution of carminic acid (Table ), which was recently characterized to involve the hydrogenation of CO bond for analytes adsorbed at the surface of the corona discharge electrode . The presence of surface-assisted reactions has profound implications on the mechanism of (M + H) + and M •+ ions formation, which may include field ionization and field-induced proton transfer reactions (M •+ (surf) + H 2 O → [M + H] + + HO • ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…This is exemplified by the detection of [M + H 2 + H] + species from methanol solution of carminic acid (Table 1), which was recently characterized to involve the hydrogenation of CO bond for analytes adsorbed at the surface of the corona discharge electrode. 34 The presence of surface-assisted reactions has profound implications on the mechanism of (M + H) + and M •+ ions formation, which may include field ionization and fieldinduced proton transfer reactions (M •+ (surf) + H 2 O → [M + H] + + HO • ). Another unique feature of the proposed setup is that biosamples can be reanalyzed by repeated cycles of incapillary extraction and ionization.…”
Section: Analytical Chemistrymentioning
confidence: 99%
“…Therefore, the sample introduction method needs to turn the target analyte into the gas-phase. According to the different states of the analyte, various sample introduction methods are required including direct sampling (for gas-phase samples), headspace sampling (for volatile substances in liquid or solid phase), nebulizer (for liquid-phase samples), and thermal desorption (TD, for liquid or solid-phase samples) [ 29 , 30 , 31 , 32 ]. However, in most cases, the analyte flow is in direct contact with the discharge needle, which may result in undesired ion fragmentation and further complicate the mass spectrum.…”
Section: Introductionmentioning
confidence: 99%